PENGARUH KOMBINASI PUPUK KANDANG AYAM dan PUPUK KANDANG SAPI TERHADAP PERTUMBUHAN dan PRODUKSI TANAMAN BAWANG MERAH (Allium ascalonicum L.) VARIETAS BATU IJO - Efron Evantius Sinaga; Donatus Dahang; Sumatera Tarigan (Universitas Quality, 2021)
This research aims to determine the effect of combination of chicken manures and cow sheds to growth and production batu ijo shallot of varieties. The research was carried out in the field of Horticultural Seed Main Unit Kutagadung Berastagi, Berastagi District, Karo Regency, North Sumatra, in the elevation of ± 1,350 m above sea level. The research was conducted in June 2019 - August 2019. This research used the Non Factorial Randomized Block Design (RBD) method, was aplied: a combination of chicken manures and cow sheds, symbol (K): control (K0), 100% chicken coop (K1), 80% chicken coop + 20% cow shed (K2), 60% chicken coop + 40% cow shed (K3), 40% chicken coop + 60% cow shed (K4), 20% coop chicken + 80% cow shed (K5) and 100% cow shed (K6), seven treatments and four replications. Data obtained were performed analysis of variance with a F test of 5% level. The significant difference (p <0.05), results would be to the DMRT test. The results shownd that the treatment of the combination of chicken manure and cow shed had a significant effect (p <0.05) on the variable growth of plant height, number of leaves, number of tillers, number of tubers, tuber diameter, production per sample, and production per plot. Howere the highest average was found in the treatment of 100% chicken coops (K1) and followed the treatment of 100% cow pens (K6).